Visualization of the Business Model Concept from the View of Investors - Weijian LIU; Takayuki SAKAI (AAOS Transactions)
In recent years, the business model concept has been gaining attention in the finance sector. In 2013, the disclosure of business model information as non-financial information became mandatory in the UK market. Following this, disclosure of business model information has been recommended in Europe. The concept “Business model” has become an important concept in management studies and has received a lot of attention in the business world.In this study, we investigate how investors perceive business models. Specifically, we use KH coder to analyze transcriptions from a quantitative perspective to visualize the overall picture of business model concepts as perceived by investors and to explore the multifaceted nature of how they are perceived.As the result, we found that the important keywords of business models that are common to different positions and the interconnectedness of concepts related to business models differ depending on the position. For institutional investors, a business model is a tool used to predict and foresee the future, unlike quantitative financial information that shows past performance. It was also suggested that it is necessary to consider the aspect of value creation and the aspect of value acquisition together.